Efficacy and safety of Xiaoyao San in the treatment of chronic fatigue syndrome: a systematic review and meta-analysis - Wang, Qianqian; Zhou, Jian; Gong, Guanwen (Frontiers in Pharmacology, 2025)
BackgroundXiaoyao San (XYS) has been increasingly used in China for treating chronic fatigue syndrome (CFS), but its efficacy and safety remain unclear.ObjectiveTo systematically evaluate the efficacy and safety of XYS compared to standard biomedical treatments (SBT) in CFS patients.MethodsA comprehensive search of English and Chinese databases was conducted up to December 2024. Eligible studies included randomized controlled trials comparing XYS or XYS + SBT to SBT alone. Primary outcomes were effective rate (ER) and fatigue scale-14 (FS-14). Secondary outcomes included self-rating anxiety scale (SAS), self-rating depression scale (SDS), and adverse events (AEs). Data were analyzed using Review Manager 5.4, and evidence quality was assessed using the GRADE approach.ResultsSix studies involving 623 patients were included. The meta-analysis showed that XYS-based interventions significantly improved ER (RR = 1.27, 95% CI: 1.18–1.37, I2 = 0%) and FS-14 (MD = 1.77, 95% CI: 1.49–2.06, I2 = 54%). Subgroup analyses confirmed consistent efficacy for both XYS vs. SBT and XYS + SBT vs. SBT. Anxiety and depression improved significantly in the XYS + SBT group, with SAS (MD = 5.16, 95% CI: 3.84–6.48, I2 = 24%) and SDS (MD = 4.62, 95% CI: 3.15–6.09, I2 = 0%). Additionally, the risk of AEs was significantly reduced in the XYS + SBT group compared to SBT alone (RR = 0.48, 95% CI: 0.32–0.72, I2 = 0%). However, the quality of evidence was rated “low” due to risk of bias and potential publication bias among the studies.ConclusionXYS, whether alone or with SBT, is effective and safe for improving ER, fatigue, anxiety, and depression in CFS patients. However, due to the low quality of the evidence, results should be interpreted cautiously. High-quality RCTs with larger sample sizes and longer follow-up are needed to provide stronger evidence for the clinical use of XYS in managing CFS.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=493084, identifier CRD42023493084.